Армия государства Российского и защита Отечества - Смирнов В. В. (Просвещение, 2004)
Экземпляры: Ф24 (20231129) / Инвентарный номер: 38759 / Цена: 354.42 / Сис.шифр: 68.49(2Рос) / Авт.знак: А 83 / ГРНТИ: 78 / ББК: 68.49(2Рос)